Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), dan Dana Alokasi Khusus (DAK) terhadap Belanja Modal di Kota/Kab Provinsi Jawa Tengah (Periode 2021-2023) (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Regional autonomy is the granting of broad authority by the central government to local governments to manage their own households with the least possible interference from the central government. The study aims to see the effect of Regional Original Revenue (PAD) and Special Allocation Funds (DAK) on Capital Expenditures in Cities / Districts of Central Java Province. The population in this study is the Regency / City of Central Java Province consisting of 35 Regencies / Cities. This study uses secondary data in the form of APBD realization reports from 2021 to 2023. The analysis technique used is multiple linear regression analysis. Based on the results of this study, it shows that Regional Original Revenue and General Allocation Fund have a significant positive effect on Capital Expenditure. It can be interpreted that the higher the Regional Original Revenue and the General Allocation Fund obtained, the greater the Capital Expenditure allocated by the region. The Special Allocation Fund shows a significant positive effect on capital expenditure.